Upaya Peningkatan Kesadaran Hukum Melalui Pendaftaran Merek Bagi Pelaku Usaha Kecil Menengah Berbasis Mahasiswa - Makbul, Mohammad; Makhrus, M; Fathaniyah, Lidia (CV Litera Inti Aksara, 2023)
This article addresses the crucial issue of legal protection for products and services by business entities, known as intellectual property. In the effort to value and safeguard intellectual creations, the concept of Intellectual Property Rights (IPR) emerged with the aim of providing recognition, appreciation, and protection to these creations, also contributing to economic growth. The Directorate General of Intellectual Property Rights (IPR) is responsible for managing the administration of copyrights, trademarks, patents, and others. Trademark registration also serves as a symbol of business legitimacy, reducing risks and enhancing consumer trust in products. The article highlights the urgency of intellectual property registration, particularly in sectors requiring legal protection. In light of this, community engagement is conducted to impart understanding to small and medium-sized business operators among students and provide training on business trademark registration. The method employed in this community engagement involves participatory dialogue-based socialization and trademark registration training. The outcomes of this community engagement reveal that many students engaged in small and medium-sized businesses lack business legitimacy. Hence, there is a need for trademark registration training to be conducted.